Mitochondrial cytochrome c oxidase subunit I gene analysis of the yellowfin snapper, Lutjanus xanthopinnis in the Indo-Pacific region and a note on Lutjanus lutjanus population structure - Takaomi Arai; Hussein Taha; Najihah Alidon; Juhaidah Jumat; Syakirah Azmey; Nur Dhabitah Zan; Tun Nurul Aimi Mat Jaafar; Ahasan Habib (Heliyon, 2023)
The yellowfin snapper, Lutjanus xanthopinnis, was recorded as a newly described species in the Indo-Pacific region in 2015. However, the knowledge of its biology, biogeography and ecology is scarcely understood, and, hence, its current conservation status is categorized as Data Deficient. The mitochondrial cytochrome c oxidase subunit I (COI) gene was examined to confirm species identification. We also examined the COI gene haplotypes of L. xanthopinnis in Brunei Darussalam and Malaysia together with other waters, i.e., Bangladesh, Indonesia, Japan, Singapore, Sri Lanka and Taiwan. Our molecular analyses found that Brunei Darussalam and eastern Peninsular Malaysia samples were genetically similar. However, the former showed higher genetic diversity than the latter. The samples from these two sites also showed signatures of population expansion. Furthermore, identical haplotypes could be found in different locations, suggesting the absence of spatial genetic structure. On the other hand, Lutjanus lutjanus showed a population structure associated with geographical locations, i.e., western Pacific Ocean, Indian Ocean and Maluku in Indonesia.